Muserator: Interactive App Empowering Curators in Museum Exhibition Content Design - Rosli, Hafizah; Kamarudin, Norfadilah; Isa, Badrul (Research in Management of Technology and Business, 2024)
Due to digitisation, museum exhibitions are evolving, with digital stories becoming vital for cultural education. Muserator offers a guideline for curators to create engaging digital content, particularly in Malaysian museums. Through qualitative research, this interactive application provides insights and tools for developing historical and cultural narratives. Future curators can enhance museum exhibitions by integrating Muserator into visual culture courses, fostering participatory experiences. This research supports museum educational advancements, aligns with SDG 4, Quality Education, and promotes lifelong learning opportunities.